Implementation of the Fuzzy AHP, PROMETHEE II, and VIKOR Methods in Selecting Priority Projects in the Utilities Area of the PT ABC Refinery - Nugraha, Dwiky; Ratnasari, Vita; Bayuaji, Ridho; Agung Wahyuono, Ruri (Journal Research of Social Science, Economics, and Management, 2026)
The Utilities Plant at PT ABC’s LNG Plant has experienced declining reliability due to aging infrastructure. Data from the 2019–2024 period showed that 8 out of 13 Process Train operational failure cases were attributed to utility area failures, resulting in losses amounting to hundreds of billions of rupiahs. Capital investment evaluation (CAPEX) has traditionally focused primarily on financial indicators without incorporating non-financial parameters. This study applied a three-stage hybrid multicriteria decision-making (MCDM) model consisting of Fuzzy Analytical Hierarchy Process (FAHP) based on Buckley’s approach, PROMETHEE II, and VIKOR to optimize the selection of eight strategic project alternatives. The FAHP results identified Safety (35.06%) and Reliability (22.48%) as the highest-priority criteria. The PROMETHEE II method ranked HV Transformer Replacement (A3) as the first priority (net flow = +0.5308) and DCS Upgrade (A2) as the second priority (net flow = +0.5223). However, the Acceptable Advantage test in the VIKOR method indicated a very small difference in the compromise index (?Q = 0.0469 < 0.1429), suggesting that the ranking difference between the top alternatives was not sufficiently significant. Sensitivity analysis within the ±5% range resulted in shifts in the priority rankings, confirming the interdependence between power supply reliability and control automation systems. This study recommends HV Transformer Replacement (A3) and DCS Upgrade (A2) as co-priority project alternatives for implementation.